More Fiscal Resources for Infrastructure? Evidence from East Africa - Briceño-Garmendia, Cecilia (World Bank, Washington, DC, 2012)
This paper evaluates the extent of fiscal resource availability for infrastructure in four East African countries and explores the main options for its expansion. A number of major channels will be examined. The first is the extent to which expenditure is well allocated across sectors, sub-sectors, expense categories, jurisdictions and geographic areas. The second is the extent to which there is scope for improving efficiency by enhancing the operational performance of state owned enterprises (SOEs), restoring adequate levels of maintenance, or improving the selection and implementation of investment projects. The third is the extent to which user charges are applied and set at levels consistent with cost recovery. The fourth is the extent to which private sector participation has been fully exploited as a vehicle for raising investment finance. While it is difficult to evaluate these things very precisely, a number of proxy indicators are used to shed light on the matter.